Interrater reliability for sleep scoring according to the Rechtschaffen & Kales and the new AASM standard - DANKER‐HOPFE, HEIDI; ANDERER, PETER; ZEITLHOFER, JOSEF; BOECK, MARION; DORN, HANS; GRUBER, GEORG; HELLER, ESTHER; LORETZ, ERNA; MOSER, DORIS; PARAPATICS, SILVIA; SALETU, BERND; SCHMIDT, ANDREA; et al. (Journal of sleep research, 2009)
Summary Interrater variability of sleep stage scorings has an essential impact not only on the reading of polysomnographic sleep studies (PSGs) for clinical trials but also on the evaluation of patients’ sleep. With the introduction of a new standard for sleep stage scorings (AASM standard) there is a need for studies on interrater reliability (IRR). The SIESTA database resulting from an EU‐funded project provides a large number of studies (n = 72; 56 healthy controls and 16 subjects with different sleep disorders, mean age ± SD: 57.7 ± 18.7, 34 females) for which scorings according to both standards (AASM and R&K) were done. Differences in IRR were analysed at two levels: (1) based on quantitative sleep parameter by means of intraclass correlations; and (2) based on an epoch‐by‐epoch comparison by means of Cohen’s kappa and Fleiss’ kappa. The overall agreement was for the AASM standard 82.0% (Cohen’s kappa = 0.76) and for the R&K standard 80.6% (Cohen’s kappa = 0.68). Agreements increased from R&K to AASM for all sleep stages, except N2. The results of this study underline that the modification of the scoring rules improve IRR as a result of the integration of occipital, central and frontal leads on the one hand, but decline IRR on the other hand specifically for N2, due to the new rule that cortical arousals with or without concurrent increase in submental electromyogram are critical events for the end of N2.